Perencanaan Pengelolaan Sampah Di Pasar Dasan Agung Kota Mataram Dengan Pendekatan Reduce, Reuse Dan Recycle (3R) - Wahyudin Wahyudin; Fitriah Fitriah; Azwaruddin Azwaruddin (Jurnal Serambi Engineering, 2020)
Waste management in the Dasan Agung Market in Mataram City still uses conventional patterns. This pattern is not in line with the NTB Province policy that launched the concept of zero waste in 2019-2023. One approach that can support the program is the 3R method of waste management. This study aims to develop a waste management plan using the 3R approach. The method used in this study is the observation method, which is observing the current conditions and measuring the generation and composition of waste. The technique of determining the sample and measurement time and the procedure refers to SNI-19-3964-1995. The results showed that the amount of solid waste generation in Dasan Agung Market was 2.7 m3 / day and the weight of solid waste was 467 kg / day. Waste composition was obtained by organic waste 52.60% and inorganic waste 47.40%. TPS 3R is planned with an area of 110 m2, namely 74 m2 for composting area and 36 m2 for sorting and handling inorganic waste, and residual waste. The composting system implemented is using the drum method with a capacity of 100 liters, a total of 307 pieces. Waste Management Planning using the 3R Approach is capable of handling 80% of the waste, and 20% of the residue is disposed of in the landfill.